Toward the Construction of 3D Dipeptide-Metal Frameworks - Emami, Seyedali
Single amino acids have been vastly used to generate metal-biomolecule frameworks. Three-dimensional (3D) frameworks based on di- and tripeptide frameworks remain nevertheless quite scarce. We report the preparation of unique 3D dipeptide-metal frameworks in which both amino acid residues participate in metal coordination and in the construction of the networks.